Additions to the family Junewangiaceae (Sordariomycetes): novel species and new records from freshwater habitats in Southwestern China - Wen-Peng Wang; Chuan-Gen Lin; Ting-Xiang Liu; Hong-Wei Shen; Zong-Long Luo; Zong-Long Luo (Frontiers in Microbiology)
Junewangiaceae (Sordariomycetes) is a family with a relatively recent taxonomic history and a small number of described species. However, a major challenge within this family is the inability to distinguish between various genera based solely on the phylogenetic analysis. In this study, we introduced two new species, Junewangia guangxiensis and J. synnematica, which formed independent clades in phylogenetic analysis and displayed characteristics that were easily distinguishable from other species within this family. Additionally, three previously known species, viz., Dictyosporella aquatica, D. thailandensis, and J. thailandensis, are reported from China for the first time. Furthermore, D. bambusicola is documented from a freshwater habitat. The results enhance our understanding of Junewangiaceae and provide some suggestions for addressing the taxonomic problems of this family in the future.